Ts. Dr. Norazlianie produces high-purity hydrogen gas for power industry - Hafizatulazlin, Abdul Aziz; Nurhartini, Mohd Hatta (2021)
GAMBANG, 6 July 2021 - Hydrogen is currently gaining the attention of many countries due to its high efficiency, high energy density and use in the energy industry.